2020
DOI: 10.1016/j.seppur.2020.116966
|View full text |Cite
|
Sign up to set email alerts
|

Membranes based on polyacrylamide coatings on metallic meshes prepared by a two-steps redox polymerization. Performance for oil-water separation and biofouling effects

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Grafting, [180] coating, and acid-base treatment are the most widespread chemical methods used for membrane external surface modification, as shown in Figure 9a,b compared with Figure 9c for blending mentioned before. Because external physical treatment to surface modification for membranes includes but is not limited to plasma irradiation, ion beam irradiation, and vapor phase deposition techniques.…”
Section: External Treatment For Membrane Surface Modificationmentioning
confidence: 99%
“…Grafting, [180] coating, and acid-base treatment are the most widespread chemical methods used for membrane external surface modification, as shown in Figure 9a,b compared with Figure 9c for blending mentioned before. Because external physical treatment to surface modification for membranes includes but is not limited to plasma irradiation, ion beam irradiation, and vapor phase deposition techniques.…”
Section: External Treatment For Membrane Surface Modificationmentioning
confidence: 99%
“…Hence, scholars have made significant efforts and found that compared with the traditional oil–water separation materials, the superwetting separation materials demonstrate high purity, environmental protection, low cost, and simple operation for emulsion separation 11–13 . Considering these advantages, researchers have successfully formulated a few two‐dimensional (2D) superwetting separation materials, including metal‐mesh, fiber membranes, biological fabrics, and polymeric membranes, which can perform decent emulsion separation 14–17 . The accepted separation mechanism using these superwetting materials is a simple screening filtration mechanism, 18 wherein the oil and water phases have different surface tension on the pore of the separation material.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these advantages, researchers have successfully formulated a few two-dimensional (2D) superwetting separation materials, including metal-mesh, fiber membranes, biological fabrics, and polymeric membranes, which can perform decent emulsion separation. [14][15][16][17] The accepted separation mechanism using these superwetting materials is a simple screening filtration mechanism, 18 wherein the oil and water phases have different surface tension on the pore of the separation material. Hence, the pore size of the separation material must be lower than the droplet size.…”
mentioning
confidence: 99%
“…Polyacrylamide (PAM) is highly hydrophilic, which contains a large number of amino groups, and its coatings can be prepared without any additional organic solvents. [30,31] Silica (SiO 2 ) is one of the most commonly used inorganic particles to construct the surface with micro-nanostructures. Silica sol is a dispersion of nanoscale silica particles in water.…”
Section: Introductionmentioning
confidence: 99%